Histamine promotes angiogenesis through a histamine H1 receptor-PKC-VEGF-mediated pathway in human endothelial cells - Omer Faruk Hatipoglu; Takashi Nishinaka; Masahiro Nishibori; Masahiro Watanabe; Takao Toyomura; Shuji Mori; Kursat Oguz Yaykasli; Hidenori Wake; Hideo Takahashi (Elsevier, 2023)
Histamine is a well-known inflammatory mediator, but how histamine induces angiogenesis remains poorly understood. In the present study, we demonstrated a dose-dependent dynamic tube formation in the human endothelial cell line EA.hy926 in the presence of histamine that was completely blocked by histamine H1 receptor (H1R) and protein kinase C (PKC) inhibitors. However, histamine H2, H3, and H4 receptor inhibitors did not inhibit tube formation, suggesting that H1R-PKC signaling is involved in histamine-induced tube formation. Moreover, we found an H1-specific induction of vascular endothelial growth factor (VEGF) expression. Inhibition of VEGF receptor 2 (VEGFR2) suppressed the histamine-induced tube formation, indicating that VEGF is downstream of histamine signaling. Additionally, we demonstrated that histamine stimulation induces the expression of critical regulators of angiogenesis such as matrix metalloproteinase (MMP)-9 and MMP-14 metalloproteases, as histamine-induced tube formation is blocked by MMP inhibitors. In summary, our study indicates that histamine can activate the H1R in human endothelial cells and thereby promote tube formation through the PKC, MMP, and VEGF signaling pathways.